New distribution records and variation of the two common lowland salamanders Bolitoglossa colonnea (Dunn, 1924) and B. lignicolor (Peters, 1873) in Panama (Amphibia: Caudata: Plethodontidae) - Andreas Hertz; Sebastian Lotzkat; Gunther Köhler (Check List, 2013)
We revise the geographic distribution of two common lowland salamanders in western Panama. We close the widest gap in the known distribution of Bolitoglossa colonnea with a first record for the province of Veraguas and extend its known vertical distribution to a third life zone. For B. lignicolor we present additional localities in the province of Chiriquí and the first record from Comarca Ngöbe-Buglé that close the gap between extreme western Panama and the Azuero Peninsula. We present morphological, molecular, and coloration data for both species.